Evaluation of hemodynamic and SpO2 variability during different stages of periodontal surgery - Babak Amoian; Mozafar Rabíee; Maral Aghvami; Shabnam Milani (Wolters Kluwer Medknow Publications, 2013)
Background: Changes in pulse rate and blood pressure are common consequences during oral surgeries. Hypoxia during surgical process is another side effect. The objective of the present study was evaluation of blood hemoglobin oxygenation and hemodynamic changes during periodontal surgery. Materials and Methods: This clinical trial study was conducted upon 50 subjects aged 30-55 years who referred to the clinic of dental faculty of Babol University and needed periodontal surgery with modified widman flaps in the anterior section of the maxilla. Pulse rate, blood pressure, and pulse oximetric evaluations were recorded in five stages during surgery. Results: The average of systolic and diastolic blood pressure had been in their maximum amount in the second stage of evaluation and minimum amounts were in the first one; while pulse rate changes were greatest in the second stage and lowest in the fifth stage. Analyzing the data revealed no significant difference in Blood Oxygen Saturation (SpO2) measurements in none of the stages evaluated. Conclusions: Blood pressure and heart rate increased significantly after the injection of anesthetic drug and in further phases they were decreased after the elimination of stimulating effect of adrenaline. SpO 2 changes were not significantly prominent.